1987
DOI: 10.3382/ps.0661197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fructose on Broiler Chick Performance

Abstract: The effect of feeding various levels of dietary fructose, furnished by high fructose corn syrup (HFCS), to broiler-type chicks housed in Petersime batteries was studied in two experiments. In experiment 1, HFCS was added to a corn-soybean meal basal diet at levels of 0, 5, 10, and 15%. In Experiment 2, HFCS was added to the diet at levels of 0, 2, 4, 6, and 15%. In both experiments diets were isocaloric and isonitrogenous. In Experiment 1, chicks fed HFCS consumed more feed (P less than or equal to .05) and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Studies have shown that the addition of glycine to low-protein diets can increase the growth efficiency of broilers, and the growth performance is comparable to that with normal protein diets [17][18][19]. The supplementation of fructose in broiler diets not only improves palatability, but also improves the performance of broilers [20]. Sucrose, as a safe nutritive sweetener, can improve the activity of amino acids and promote the synthesis of proteins by increasing the energetic synthesis [21][22][23].…”
Section: Analysis Of Yc Componentsmentioning
confidence: 99%
“…Studies have shown that the addition of glycine to low-protein diets can increase the growth efficiency of broilers, and the growth performance is comparable to that with normal protein diets [17][18][19]. The supplementation of fructose in broiler diets not only improves palatability, but also improves the performance of broilers [20]. Sucrose, as a safe nutritive sweetener, can improve the activity of amino acids and promote the synthesis of proteins by increasing the energetic synthesis [21][22][23].…”
Section: Analysis Of Yc Componentsmentioning
confidence: 99%